Measuring emotional response towards aroma attributes in beer; a comparison of self-report, physiological and facial expression measures - Beyts, Camilla (2016)
Emotion research within Sensory Science is at a cross roads. Some investigations have solely focused on explicit measures of emotional response, asking consumers to self-report their emotions. Others have focused on implicit measures such as changes in physiological and facial expression to capture the consumer’s unconscious responses. However the discrimination ability of implicit and explicit measures has seldom been compared. The aim of this project was to compare physiological/facial expression, self-reported emotional response and traditional hedonic liking scores to determine which measure was more discriminating towards a range of beer aromas. Two preliminary investigations assisted in the development of an experimental protocol and helped to define the number of replicates required for the main study. Implicit measures included changes in heart rate, skin temperature and electromyography recordings from two facial muscles; the corrugator supercilli and zygomatic major. Preliminary investigations also highlighted the need to include a range of pleasant and unpleasant aromas and promoted the use of an emotional lexicon specific to beer which would allow greater discrimination between aromas than more simple measures of valence and activation. Learnings from the preliminary stages were subsequently applied to the larger main investigation. The main investigation compared changes in physiological/facial expression, self-reported emotional response and hedonic liking towards a series of pleasant, neutral and unpleasant aromas within beer. The results revealed that corrugator and zygomatic activity could discriminate between unpleasant and pleasant or unpleasant and neutral samples respectively. However physiological measures were non-discriminating. Liking scores were found to be more discriminating than facial expression measures, allowing the distinction between pleasant and neutral samples. However self-reported emotional response was found to be the more discriminating than both liking and facial expression measures, allowing discrimination between pleasant and neutral samples as well as between the pleasant samples themselves. This project found that self-reported emotional response provided the greatest discrimination between beer aromas and was found to be most discriminating compared with liking and physiological/facial expression measures of emotion. Consequently self-reported emotional response is recommended for studies which require a high degree of product discrimination. The ability for self-reported emotional response to distinguish between pleasant aromas is of particular interest to industry where commercial products may be poorly discriminated on the basis of liking alone.